Adenylate and Nicotinamide Nucleotides in Developing Soybean Seeds During Seed-Fill - Quebedeaux, Bruno (1981)
Profiles of adenylate and nicotinamide nucleotides in soybean seeds were determined during seed-fill. The ATP content per seed increased during the early seed-filling stages to a level of 10 to 12 micrograms per seed. Seed ATP decreased after 40 days of development and reached its lowest level of less than 1 microgram at maturity. The ATP:ADP ratios were relatively constant at all seed development stages. Sharp increases in AMP levels during the late seed-fill stages were paralleled with a disappearance of ATP and ADP pools resulting in a reduced seed energy charge. Energy charge varied from the highest value of 0.78 at mid-seed-fill to less than 0.10 at maturity. Of the oxidized (NAD, NADP) and reduced (NADH, NADPH) nicotinamide nucleotide forms, NAD was the most abundant. Levels as high as 17.5 micrograms per seed were observed during the mid-seed-filling stages. NADP was found almost exclusively in the reduced form with a NADP: NADPH ratio of less than 0.35, whereas the reverse was noted for NAD which was found mainly in the oxidized form with a NAD:NADH ratio in the range of 5 to 25. NADP was detected in low concentrations compared to the other adenylate and nicotinamide nucleotides. The nicotinamide redox charge defined as (NADH + NADPH)/(NAD + NADH) + (NADP + NADPH) was calculated to express the state of the energy balance between the oxidized and reduced nicotinamide nucleotide forms. The nicotinamide redox charge varied between 0.15 and 0.30 during seed development and was significantly lower than that found for the adenylate energy charge.